Polydatin exerts therapeutic effects on myelodysplastic syndrome by inhibiting the protein expression of oncogenes via hypermethylation in vitro - Qingbing Zhou; Yuanbin Liang; Ruofan Chen; Hongzhi Wang; Qiuyue Guo; Li Liu; Xiaobo Zhu; Fengqin Xu (Scientific Reports)
Abstract DNA methylation plays a critical role in myelodysplastic syndrome (MDS). Here, we aimed to observe the effects of polydatin (PD) on DNA methylation in MDS cells on a genome-wide scale and explore the underlying mechanisms, providing new evidence for PD as a novel hypermethylation agent. We used the Gene Expression Omnibus (GEO) online database to evaluate the DNA methylation characteristics of MDS patients. A Human Methylation 850 K BeadChip was used to evaluate the effects of PD on DNA methylation in SKM-1 cells. Western blotting (WB) was used to observe changes in the expression of related proteins. Cytoscape was used to determine the key genes that were hypermethylated by PD. The therapeutic effects were evaluated using flow cytometry experiment and a cell counting kit-8 (CCK-8) assay in vitro. Data from the GEO online database revealed that aberrant gene hypomethylation plays an important role in MDS. In MDS cells, 448 genes (71.91%) were hypermethylated following PD treatment. These hypermethylated genes are related to cancer-related signaling pathways. Moreover, key hypermethylated genes, including PIK3CA, ITPR3 and SPOPL, were identified, and these three genes are all oncogenes. Most importantly, PD decreased the protein expression of the above three oncogenes. Finally, we found that PD could inhibit the proliferation of MDS cells, arrest them in the S phase and induce their apoptosis. Our findings demonstrated that PD has therapeutic effects on MDS by inhibiting the protein expression of oncogenes via hypermethylation in vitro, indicating that PD may be a novel hypermethylation agent.